2006
DOI: 10.1007/11866565_93
|View full text |Cite
|
Sign up to set email alerts
|

A Novel MRI Texture Analysis of Demyelination and Inflammation in Relapsing-Remitting Experimental Allergic Encephalomyelitis

Abstract: Abstract.We have developed a novel multiscale localized image texture analysis technique, based upon the polar Stockwell Transform (PST). In this paper we characterized image texture in vivo using the PST in histologically verified lesion areas in T2-weighted MRI of an animal model of multiple sclerosis. Both high and low frequency signals, representing inflammation and demyelination, were significantly increased in pathological regions compared to normal control tissue. This suggests that this new local spati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 14 publications
1
8
0
Order By: Relevance
“…In particular, Zhang et al [6] characterized image texture in vivo using the polar S-Transform (pST) of histologically verified multiple sclerosis lesions within T2-weighted MRI. Both high and low frequency components, representing inflammation and demyelination, were significantly elevated in pathological regions compared to normal control tissue.…”
Section: Related Researchmentioning
confidence: 99%
“…In particular, Zhang et al [6] characterized image texture in vivo using the polar S-Transform (pST) of histologically verified multiple sclerosis lesions within T2-weighted MRI. Both high and low frequency components, representing inflammation and demyelination, were significantly elevated in pathological regions compared to normal control tissue.…”
Section: Related Researchmentioning
confidence: 99%
“…Assessment of serial T2‐weighted MRI reveals that texture is finer in normal myelin and remyelinated lesions than in demyelinated lesions, and that the time course of MRI texture is concordant with the evolution of myelin integrity in these animals . Similarly, in mice with experimental allergic encephalomyelitis, abnormally increased lesion texture corresponds to greater tissue injury . The pathological substrates of texture measurements in human MS, however, have never been studied.…”
mentioning
confidence: 99%
“…By using the Stockwell transform, they have shown that low frequency information can be a useful means to quantify lesion injury and recovery in MS. In an animal model of MS, Zhang et al (2006) have additionally shown that frequency information can be directly related to histopathological changes in lesions. As expected, classifier performance was best for lesion matter, for both global and local analyses of anisotropy.…”
Section: Discussionmentioning
confidence: 96%